The Indonesian Terms of Disease Names: A Corpus Linguistic Study - Hernina Hernina; Yenny Karlina; Devi Ambarwati Puspitasari (IAIN MADURA, 2023)
The Indonesian terms of disease names are unique. Despite being different from their medical terms, Indonesian terms of disease names contain elements of figurative language. This study aims to analyze stylistic naming. The data were Corpora from articles, social media forums, and online news on health for 2013-2023, involving 1.206.281.985 tokens from the Indonesian-Leipzig Corpora Collection (ILC) and 39.294 tokens collected for the 2023 Health Forum Corpus (HF). Data analysis concerned the wordlist and collocation feature to see the frequency, trend, and pattern, and the concordance feature examined the language style of the names. The study does not find any evidence of changes in health terms over the past decade, such as “penyakit jantung” (heart disease),